2022
DOI: 10.21037/jtd-22-595
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the evaluation of tracheal length using a three-dimensional imaging workstation

Abstract: Background: Limited information is available on the total tracheal length and its other characteristics for tracheal surgery. This study aimed to investigate the reference value of tracheal length and assess its relationship with physiological variables. Methods:We measured the tracheal length of 215 patients (107 men and 108 women) who underwent contrast-enhanced computed tomography before thoracic surgery using a three-dimensional imaging workstation. Pearson correlation analysis and multiple linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…These indications are bene cial for anesthesiologists when deciding the type and xation depth of tracheal tubes. Although this was a single-center study performed in Japan and all patients were Asian, the mean tracheal length was similar to that in other reports from Japan and those from other countries, such as England, New Zealand, and East Asian countries [25][26][27][28][29][30], and the mean tracheal length might be similar across populations. Thus, the characteristics and positional relationships between a tracheal diverticulum and the tracheal tube in this study could be extrapolated to other populations.…”
Section: Discussionsupporting
confidence: 85%
“…These indications are bene cial for anesthesiologists when deciding the type and xation depth of tracheal tubes. Although this was a single-center study performed in Japan and all patients were Asian, the mean tracheal length was similar to that in other reports from Japan and those from other countries, such as England, New Zealand, and East Asian countries [25][26][27][28][29][30], and the mean tracheal length might be similar across populations. Thus, the characteristics and positional relationships between a tracheal diverticulum and the tracheal tube in this study could be extrapolated to other populations.…”
Section: Discussionsupporting
confidence: 85%
“…Unlike Mi et al. who measured directly from coronal CT images, we employed 3D reconstruction technology to assess the central axis length of the tracheobronchial tree airways ( Figure 1B ), minimizing random errors from different starting points and coronal image positions, and reducing systematic errors related to airway curvature and the angles between the trachea and the coronal plane [ 4 ]. In contrast to Ge et al.’s study [ 14 ], which used bronchoscopy to measure central airway lengths in Chinese adults, our study found a shorter tracheal length but a longer main bronchus length.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we utilized 3D reconstruction technology to model the tracheobronchial tree and determined SCA by measuring the angle between the midlines of the main bronchial lumens ( Figure 1A ). This method not only significantly reduces measurement errors inherent in 2D chest CT imaging but also provides more accurate results that reflect clinical realities, such as the actual pathways during the use of airway devices, intubation, or other airway-related surgeries [ 4 , 6 , 7 ]. However, our study did not independently measure RA and LA, which may limit a comprehensive analysis of sex differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation